PROXIMATE COMPOSITION OFTHE MUSSEL(Pilsbryoconcha exilis) COLLECTED IN SUNGAI PAKU VILLAGE - Deevrizal Deevrizal; Bustari Hasan; N. Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTPilsbryoconcha exilis,a type of mussel, was commonly found in ponds and rivers of Sungai Paku Village, Kampar District, Riau Province.This research wasaimedto evaluateand to compare the proximatecompositionof  themusselcollected from rivers and ponds.The used method in this researchwas a survey method with randomsampling that wascollectedfrom rivers and ponds.The protein, moisture, water, ash, and carbohydrate of the mussel meat collectedfrom rivers consecutively were 14.29%, 0.56%, 78.21%, 1.26%, and 5.68%.Furthermore, the protein, fat, moisture, ash, and carbohydrate ofthe mussel collectedfrom ponds consecutively were 15.36%, 1.65%, 79.85%, 2.54%, and 0.6%. Based onthe results of the proximate analysis showed a significant difference with a different environment to the mussel of proximate content.Keywords:Pilsbryoconcha exilis, pond, proximate,river.